Familial skin dimples on the shoulders. - Menni, S.; Boccardi, D. (European Journal of Pediatric Dermatology, 2002)
We describe bilateral cutaneous depressions located on the shoulders of an 11-monthold baby girl and her mother. This familial, congenital pattern is rarely reported in the relevant literature and usually benign. However, physicians should remember that both shoulder dimples and dimples of other sites can be a feature of a variety of syndromes.